Influence of the ionic character of a drug on its release rate from hydrogels based on 2-hydroxyethylmethacrylate and acrylamide synthesized by photopolymerization - M. L. Gomez; R. J. J. Williams; H. A. Montejano; C. M. Previtali (eXPRESS Polymer Letters)
The influence of the ionic character of a specific drug on its release rate from a hydrogel based on 2-hydroxyethylmethacrylate (HEMA) and acrylamide (AAm) is analyzed. The hydrogel was synthesized by photopolymerization employing visible light, safranine O (Saf), as sensitizer, and a silsesquioxane functionalized with amine and methacrylate groups (SFMA), as co-initiator and crosslinker. Safranine O (Saf) was employed as a model of a cationic drug and the anionic form of resorufin (Rf) as a model of an anionic drug. Saf exhibited a larger affinity with functional groups of the hydrogel than that of Rf. This produced a lower loading and a faster release rate of Rf with respect to Saf. Besides, the release rate of Rf followed a Fickian behavior, while that of Saf exhibited a non-Fickian behavior. By hydrolyzing the hydrogel at pH = 13, amide groups supplied by AAm were irreversibly converted into carboxylic acid groups. Higher loadings and slower release rates of Saf from the hydrolyzed hydrogels were observed, making them particularly suitable for the slow drug-delivery of cationic drugs.